'AQD AL-SULTHAH WA TADAWULUH 'INDA AL-IMAM AL-KHUMAYNI (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2002)
This research tries to explore a matter of power establishment and its delegation according to Khomeini's view. Muslims agree that khilafat and imamat are Prophet's delegation in terms of preserving religion and managing worldly lift. However, the Twelver Shi'ite has a different view from most of muslims'. They are sure that the Shi'ite imams are impeccable (ma'sum) and trustees to take over for the Messenger. Their position is just like the Messenger's in the impeccability. About the period of the great occultation (al-ghaibah al-kubra), Khomeini has a different opinion from most of the Twelver Shi'ite Scholars, that the just ulamas are the ones that have the highest authority as representation of the Imam. The result of the research shows that, in terms of power establishment and its delegation, Khomeini has a different view from the other scholars.